Pengembangan Media Pembelajaran Komik Fisika Materi Pokok Pengukuran Untuk Siswa SMA Negeri 1 Compreng - Rendi Rendi; Sumaryati Sumaryati; Popi Purwanti (Navigation Physics : Journal of Physics Education, 2020)
The purpose of this study is to develop learning media for physics comics on the subject matter of measurement for class X students, to know the quality of physics comics in the developed measurement material for class X students at SMAN 1 Compreng, and to know the students responses to physics comics on the developed measurement material. This research is development research by conducting product analysis to be developed, developing initial products, expert validation and revisions, small-scale field trials and product revisions, and large-scale field trials and final products. The result of the research is the product developed in the form of Comic Physics Media, the Main Material of Measurement. The quality of the physics comic media developed according to media experts is Good (B) with a value of 3.14, according to the material experts is Very Good (SB) with a value of 3.61, according to the physics teacher is Very Good (SB) with a value of 3, 67. 3). Student responses to physics comics in limited trials obtained a percentage of 93% while in large-scale field trials obtained a percentage of 95%.